Causes of Abnormal Uterine Bleeding in Females of Reproductive Age Group attending Gynaecology Dept of UOL Hospital - Amina Saleem, Safoora Anjum, Arjamand Mahmood, Razia Kosar, Fatima Naveed, Shazia Noor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Abnormal uterine bleeding is a prevalent problem that prompts a female to seek medical help. The most common symptom of abnormal uterine bleeding is heavy menstrual bleeding. The impact of abnormal uterine bleeding on one's quality of life is important. Aim: To determine the causes of abnormal uterine bleeding. Methods: This cross-sectional study was conducted at Department of Gyneacology University of Lahore Teaching Hospital Lahore over a period of one year from Nov 2020 to Nov 2021. Eighty females of reproductive age with Abnormal Uterine Bleeding were selected. All females were examined for the etiology of abnormal uterine bleeding. The females with menstrual blood loss lasting >8 days, passage of blood clots or haemoglobin concentration < l0 gm/dl were enrolled. The exclusion criteria includes the females less than 20 years of age, or with pubertal menorrhagia or postmenopausal females. Results: Out of total eighty females, 25% females belong to 42 years age group. The most prevalent etiology of abnormal uterine bleeding was fibroid uterus i.e. 62.5% cases, followed by adenomyosis (15%), endometrial polyp (10%) and endometrial hyperplasia (12.5%). Fifty females (50%) were multipara, 20 (25%) were grand multipara and 10(12.5%) were great grand multipara. Severe anemia was noted in almost 10 females (12.5%), moderate anemia in 56 cases (70%) and mild anemia in 14 cases (17.5%). Transabdominal scan was done to confirm the diagnosis of fibroid uterus, adenomyosis, endometrial hyperplasia and endometrial polyp. Conclusion: Fibroid uterus was the commonest cause in females presenting with abnormal uterine bleeding to University of Lahore Teaching Hospital affecting quality of life in females and causing psychological problems.